The Effect Of Autocad Utilization On The Architectural Drawing Skills Of Civil Engineering Students - Ikhtiar Aroniati Daeli; Carsa Alim Lase (CV. SINAR HOWUHOWU, 2026)
The integration of Computer-Aided Design (CAD) software into engineering education has become increasingly important in developing students' technical competencies and professional readiness. This study aimed to examine the effect of AutoCAD utilization on the architectural drawing skills of civil engineering students. A quantitative research approach with an explanatory design was employed. The study involved civil engineering students who had completed engineering drawing and AutoCAD-related courses. Data were collected using structured questionnaires and architectural drawing performance assessments. The collected data were analyzed using descriptive statistics and simple linear regression. The findings revealed that the level of AutoCAD utilization among students was categorized as high, with an overall mean score of 4.23, while architectural drawing skills also achieved a high category with an overall mean score of 4.18. Regression analysis demonstrated that AutoCAD utilization had a positive and statistically significant effect on architectural drawing skills (β = 0.742, p < 0.001). The coefficient of determination (R² = 0.572) indicated that 57.2% of the variation in students' drawing skills could be explained by AutoCAD utilization. These findings suggest that frequent and effective use of AutoCAD enhances drawing accuracy, visualization ability, drafting efficiency, and compliance with engineering drawing standards. The study concludes that integrating AutoCAD into civil engineering education significantly improves students' architectural drawing competencies and better prepares graduates for the technological demands of the modern construction industry.